2018
DOI: 10.1111/1744-7917.12612
|View full text |Cite
|
Sign up to set email alerts
|

Development of internal COI primers to improve and extend barcoding of fruit flies (Diptera: Tephritidae: Dacini)

Abstract: Accurate species-level identifications underpin many aspects of basic and applied biology; however, identifications can be hampered by a lack of discriminating morphological characters, taxonomic expertise or time. Molecular approaches, such as DNA "barcoding" of the cytochrome c oxidase (COI) gene, are argued to overcome these issues. However, nuclear encoding of mitochondrial genes (numts) and poor amplification success of suboptimally preserved specimens can lead to erroneous identifications. One insect gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 39 publications
(87 reference statements)
3
14
0
Order By: Relevance
“…The analysis also revealed that the Mt-COI obtained in this study are closely related to the B. passiflorae COI in the database, with a mean p-distance of 0.0075, but are more distant from the NUMT sequences (Table 3). Similarly, the individual sequences of NUMT type 1 obtained in this study are also closely related to previously reported NUMT sequences of B. passiflorae (Krosch et al, 2020), with a mean p-distance of 0.0047 between the two groups (…”
Section: Pcr Sequencing By Cloningsupporting
confidence: 88%
See 1 more Smart Citation
“…The analysis also revealed that the Mt-COI obtained in this study are closely related to the B. passiflorae COI in the database, with a mean p-distance of 0.0075, but are more distant from the NUMT sequences (Table 3). Similarly, the individual sequences of NUMT type 1 obtained in this study are also closely related to previously reported NUMT sequences of B. passiflorae (Krosch et al, 2020), with a mean p-distance of 0.0047 between the two groups (…”
Section: Pcr Sequencing By Cloningsupporting
confidence: 88%
“…We therefore developed novel primers to specifically amplify the true Mt-COI of B. passiflorae. By cloning the PCR products of NUMT pseudogenes, we were able to determine that the NUMT copies of B. passiflorae, NUMT type 1 share 98-100% identity to the NUMT COI identified previously (Krosch et al, 2020) where the NUMT type 2 is novel sequence identified by this study.…”
Section: Numt Coi In B Passifloraementioning
confidence: 55%
“…Sequences were checked and aligned by eye in BioEdit (Hall ), any ambiguous bases were recoded as missing data and presence of pseudogenes or internal stop codons (Krosch et al . ) assessed by alignment of protein sequences in MEGA4 (Tamura et al . ).…”
Section: Methodsmentioning
confidence: 99%
“…Perrard et al (2014) confirmed that the genetic difference between wasp species had a stronger influence on the wing shape than other biotic or abiotic factors. Genetically, species complexes in genus Bactrocera are paraphyletic each other due to descent from different ancestral lines (Boykin et al, 2014;Krosch et al, 2020). However, the application of angle measure of cell br and ratio vein r-m : dm-cu could demonstrate had a lack in showing the relationship between subgenus Bactrocera and Zeugodacus as phylogenetic tree showed.…”
Section: The Angle Measurements and Comparison Of Veinmentioning
confidence: 99%